2012
DOI: 10.1186/1472-6955-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Iranian cancer patients’ perception of spirituality: a qualitative content analysis study

Abstract: BackgroundSpirituality is a subjective and multi-dimensional concept. The ambiguity in its meaning can create barriers in its application in both education and medicine. The present study aimed to explore the Iranian cancer patients’ perception of spirituality.MethodsA qualitative study, using the content analysis approach, was conducted. Semi-structured interviews were held with 11 cancer patients and six members of their families in one of Tehran’s hospitals and a charity institute. The data generated were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 24 publications
2
38
0
1
Order By: Relevance
“…Iran is a religious country and 98% of its population are Muslims [70]. Qualitative studies from Iran showed that spiritual approach is the major coping strategy to respond to cancer and Iranian cancer patients consider spirituality as a source of hope [18, 7173]. The faith component of spirituality is most often associated with religion and religious belief, whereas the meaning component of spirituality appears to be a more universal concept [74].…”
Section: Discussionmentioning
confidence: 99%
“…Iran is a religious country and 98% of its population are Muslims [70]. Qualitative studies from Iran showed that spiritual approach is the major coping strategy to respond to cancer and Iranian cancer patients consider spirituality as a source of hope [18, 7173]. The faith component of spirituality is most often associated with religion and religious belief, whereas the meaning component of spirituality appears to be a more universal concept [74].…”
Section: Discussionmentioning
confidence: 99%
“…Findings also revealed that the most common sampling technique resulted in convenience sampling (n = 11) Bentur et al 2014;Blinderman and Cherny 2005;Chio et al 2008;Coward and Kahn 2004;Hajdarevic et al 2014;Halstead and Hull 2001;Perreault and Bourbonnais 2005;Shih et al 2009;, purposive (n = 4) (Chao et al 2002;Farsi 2015;Nilmanat et al 2015;Rahnama et al 2012), snowball (n = 2) (Albaugh 2003;Lindholm et al 2002), theoretical , and intentional .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the interviews were face-to-face, with one face to face and telephone . Generally the interviews were based on open-ended questions (n = 8) Chio et al 2008;Farsi 2015;McGrath 2002;Perreault and Bourbonnais 2005;, five with in depth interviews Chao et al 2002;Farsi 2015;Shih et al 2009;, semi-structured interviews (n = 6) Hajdarevic et al 2014;Halstead and Hull 2001;Montoya-Juarez et al 2013;Perreault and Bourbonnais 2005;Rahnama et al 2012), and unstructured interview (n = 2) (Chao et al 2002;.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of spiritual therapy in terms of spiritual well-being and its relation with QOL are not well-documented. Qualitative studies from Iranian Muslim cancer patients showed that the spiritual approach is the major coping strategy by which they respond to cancer, considering that spirituality is a source of hope and peace, as reported by some independent results from Iran 2023. The faith concept of spirituality is connected with spiritual and religious belief, whereas the meaning component of spirituality may be a more universal component 24.…”
Section: The Context Of Middle Eastern Spiritual Therapymentioning
confidence: 93%